Estudo da evolução das tensões residuais através da difratometria de raios x em aço rolamento submetido a esforços cíclicos - Carvalho Filho, Eugênio Teixeira de (2015)
The micro-deformations caused by cyclic loading origins the variation of the distances between atoms of the crystal lattice producing the irreversible component. In order to study and understand the microstructural behavior of the material this paper investigated the influence suffered by residual stresses in thrust rolling bearing races fabricated in AISI 52100 steel, after tests by cyclic rolling contact in a tribometer at 1m/s under two contact pressures (500 MPa and 1400 MPa) in dry and boundary lubrication conditions. Procedures of tests thermo-acustically isolated were developed for monitoring the contact temperature and sound pressure level signals to establish a comparison between the residual stress measurements, micro-hardness Vickers and micrographic registers searching an indication of wear evolution. The sin²ψ method by X-ray diffraction technique was used to quantify the residual stresses. Three raceway zones were selected for the evaluation of wear and surface morphology after predetermined cycling, comparing with their new condition ("as received"). Micro-hardness and residual stress measurements showed significant changes after the tests and it was possible to observe the relationship between the increase of sound pressure level and the residual stress for dry and lubricated conditions.